RANCANG BANGUN SISTEM PENGANGKUT SAMPAH PADA SUNGAI SECARA OTOMATIS - Wahyuni, Irmah; Iswadi, Iswadi; Rahmaniah, Rahmaniah (Universitas Islam Negeri Alauddin Makassar, 2015)
This research aims to devise means of garbage in the river automatically and see the effectiveness of these tools. Model design made consists of conveyance of trash and garbage disposal apparatus. The working principle of this tool is if a light sensor that is placed in front of the tool covered with garbage that floats on the surface of the river. Waste transported lifted up and thrown into the garbage disposal apparatus transverse position under the position of conveyance of garbage. The results obtained from the design tool of garbage in the river is automatically obtained the maximum load that can be transported 1505,9 N while only able to practice 11,51 N with effectiveness 0,76% so that the tool is still less effective.